2022
DOI: 10.1051/0004-6361/202142911
|View full text |Cite
|
Sign up to set email alerts
|

The LOFAR view of giant, early-type galaxies: Radio emission from active nuclei and star formation

Abstract: We studied the properties and the origin of the radio emission in the most luminous, early-type galaxies (ETGs) in the nearby Universe (MK ≤ −25, recession velocity ≤7500 km s−1), as seen by the 150 MHz Low-Frequency ARray (LOFAR) observations. LOFAR images are available for 188 of these giant ETGs (gETGs), and 146 (78%) of them are detected above a typical luminosity of ∼1021 W Hz−1. They show a large spread in power, reaching up to ∼1026 W Hz−1. We confirm a positive link between the stellar luminosity of gE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Studying the properties and the origin of the radio emission in the most luminous, early-type galaxies (ETGs) in the nearby Universe with LOFAR observations, Capetti et al (2022) found that about two-thirds of the detected ETGs are unresolved, with sizes on the order of 4 kpc or lower, confirming the prevalence of compact radio sources in local universe. Because these observations are at low radio frequencies, they exclude the presence of extended steep spectrum lobes and the authors conclude that these sources are FR0 candidates.…”
Section: Introductionmentioning
confidence: 98%
“…Studying the properties and the origin of the radio emission in the most luminous, early-type galaxies (ETGs) in the nearby Universe with LOFAR observations, Capetti et al (2022) found that about two-thirds of the detected ETGs are unresolved, with sizes on the order of 4 kpc or lower, confirming the prevalence of compact radio sources in local universe. Because these observations are at low radio frequencies, they exclude the presence of extended steep spectrum lobes and the authors conclude that these sources are FR0 candidates.…”
Section: Introductionmentioning
confidence: 98%
“…For some, in particular, those obeying the FIR-radio correlation (see Section 4), radio synchrotron photons can, in principle, be produced in star-forming regions, corresponding to the observed monochromatic radio luminosities up to even ∼10 37 erg s −1 (Wrobel & Heeschen 1988;Condon et al 2002). And in fact, while for the general population of spheroids, star formation rates (SFRs) are expected to be low, meaning an SFR < 0.1 M e yr −1 , for giant ellipticals, they may reach even ∼1 M e yr −1 (Kokusho et al 2017;Capetti et al 2022). In our subsample of radio-dim sources, the SFRs estimated for some of the targets by O'Sullivan et al (2018) range from SFR ;0.004M e yr −1 for NGC 3923 up to ;0.2M e yr −1 for NGC 4636, NGC 5813 , NGC 5846, and NGC 7619.…”
Section: Discussionmentioning
confidence: 96%
“…In general, nearby bright elliptical and lenticular galaxies were long known to be radio emitters, with about one-third (or more) of a sample being typically detected at gigahertz frequencies in millijansky flux-limit surveys with a resolution of arcseconds or arcminutes (Sadler et al 1989;Wrobel & Heeschen 1991), and even a larger fraction displaying milliarcsecond-scale radio cores (Slee et al 1994). More recently, it was also established that the most massive (>10 11 M e ) or luminous (absolute K-band magnitudes < −25.5) spheroids are in fact always detected at radio frequencies (Brown et al 2011;Sabater et al 2019;Capetti et al 2022;Grossová et al 2022), even though they often lack prominent large-scale (>4 kpc) radio structures (Capetti et al 2022).…”
Section:  L Lmentioning
confidence: 99%
“…We note that the idea of having empty cavities was also considered for X-ray-mapped hot galactic and galaxy-cluster atmospheres. However, radio detections at very low frequencies indicate that the X-ray cavities are not empty, but are filled by relativistic plasmas (Giacintucci et al 2011;Bîrzan et al 2020;Capetti et al 2022;Plšek et al 2023). Yet another example of remnants of past jet activity represented by cavities filled up by relativistic plasma is provided by two giant bubbles above and below the Milky Way center, the so-called Fermi bubbles (Su et al 2010).…”
Section: Discussionmentioning
confidence: 99%